ANALISIS CAPITAL ADEQUACY RATIO TERHADAP PROFITABILITAS BANK MUAMALAT INDONESIA PERIODE 2017-2021 - Faricha Lita Nabbila; Zuraidah Zuraidah (Journal of Management and Social Sciences, 2022)
The health of a company is assessed from the capital adequacy ratio known as the Capital Adequacy Ratio. The Capital Adequacy Ratio serves as a reservoir for the risk of loss that may be faced by the bank. Capital Adequacy Ratio as a ratio that describes the ability of banks to provide funds as reserves in preventing the risk of losses experienced by banks. This ratio is useful for knowing whether a bank has very good, good, fairly good, poor, or bad health which will be very useful for policy makers. This study aims to examine in more detail the effect of the ROA, ROE, FDR, and BOPO variables on the CAR or Capital Adequency Ratio of PT Bank Muamalat Indonesia in 2017 to 2021. The analysis of this study uses a time series using the E-views 12 program and shows the results The research shows that together the ROA, ROE, FDR, and BOPO variables have a positive effect on the profitability of PT Bank Muamalat Indonesia while the variable that has a partially positive significant influence is the ROA variable while other variables such as ROE, FDR, and BOPO have no effect on CAR. or the Capital Adequacy Ratio of PT Bank Muamalat Indonesia.